Development of New Natural Lipid-Based Nanoparticles Loaded with Aluminum-Phthalocyanine for Photodynamic Therapy against Melanoma - Mello, Victor Carlos; Araújo, Victor Hugo Sousa [UNESP]; de Paiva, Karen Letycia Rodrigues; Simões, Marina Mesquita; Marques, Dafne Caroline; da Silva Costa, Nelice Roberta; de Souza, Isadora Florêncio; da Silva, Patricia Bento; Santos, Igor; Almeida, Raquel; Magalhães, Kelly Grace; da Silva, Sebastião William; et al. (MDPI, 2022)
Photodynamic therapy (PDT) mediated by photosensitizers loaded in nanostructures as solid lipid nanoparticles has been pinpointed as an effective and safe treatment against different skin cancers. Amazon butters have an interesting lipid composition when it comes to forming solid lipid nanoparticles (SLN). In the present report, a new third-generation photosensitizing system consisting of aluminum-phthalocyanine associated with Amazon butter-based solid lipid nanoparticles (SLN-AlPc) is described. The SLN was developed using murumuru butter, and a monodisperse population of nanodroplets with a hydrodynamic diameter of approximately 40 nm was obtained. The study of the permeation of these AlPc did not permeate the analyzed skin, but when incorporated into the system, SLN-AlPc allowed permeation of almost 100% with 8 h of contact. It must be emphasized that SLN-AlPc was efficient for carrying aluminum-phthalocyanine photosensitizers and exhibited no toxicity in the dark. Photoactivated SLN-AlPc exhibited a 50% cytotoxicity concentration (IC50) of 19.62 nM when applied to B16-F10 monolayers, and the type of death caused by the treatment was apoptosis. The exposed phospholipid phosphatidylserine was identified, and the treatment triggered a high expression of Caspase 3. A stable Amazon butter-based SLN-AlPc formulation was developed, which exhibits strong in vitro photodynamic activity on melanoma cells.
Keywords: Amazon butters; cancer; drug delivery systems; photodynamic therapy; third-generation photosensitizers